2014
DOI: 10.1093/molbev/msu218
|View full text |Cite
|
Sign up to set email alerts
|

Early Evolution of the Eukaryotic Ca2+ Signaling Machinery: Conservation of the CatSper Channel Complex

Abstract: Calcium signaling is one of the most extensively employed signal transduction mechanisms in life. As life evolved into increasingly complex organisms, Ca2+ acquired more extensive and varied functions. Here we compare genes encoding proteins that govern Ca2+ entry and exit across cells or organelles within organisms of early eukaryotic evolution into fungi, plants, and animals. Recent phylogenomics analyses reveal a complex Ca2+ signaling machinery in the apusozoan protist Thecamonas trahens, a putative unicel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 46 publications
0
61
1
1
Order By: Relevance
“…However, the origin and history of IP 3 R and RyR remains poorly defined. Nevertheless, it has recently been shown that many components of Ca 2+ signaling machinery are encoded in the genomes of many unicellular eukaryotes (Cai 2008; Cai and Clapham 2008, 2012; Cai, et al 2014). Whether, or how, unicellular IP 3 R and RyR-mediated signaling have contributed to the evolution and success of multicellular organisms is presently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the origin and history of IP 3 R and RyR remains poorly defined. Nevertheless, it has recently been shown that many components of Ca 2+ signaling machinery are encoded in the genomes of many unicellular eukaryotes (Cai 2008; Cai and Clapham 2008, 2012; Cai, et al 2014). Whether, or how, unicellular IP 3 R and RyR-mediated signaling have contributed to the evolution and success of multicellular organisms is presently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent bioinformatics and phylogenetic studies that surveyed the sequenced genomes of a diverse array of unicellular eukaryotic species have revealed a rich repertoire of genes encoding proteins predicted to be involved in Ca 2+ signaling and which had previously been widely presumed to be unique to higher animals (Cai 2008; Cai and Clapham 2008, 2012; Cai, et al 2014). Although these studies have highlighted sequence conservation of a number of components of the unicellular Ca 2+ machinery, functional verification of the annotated genes is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, several studies have demonstrated that age-related insulin secretion dysfunction plays an important role in glucose metabolism disorders at older ages, contributing to the high indexes of glucose intolerance in elderly populations. 20 Ca 2+ was found to play a key role in β-cell functionality, 21 and a lower intracellular level of Ca 2+ was associated with the presence of hyperglycemia and a depolarizing K + stimulus. 20 Ca 2+ was found to play a key role in β-cell functionality, 21 and a lower intracellular level of Ca 2+ was associated with the presence of hyperglycemia and a depolarizing K + stimulus.…”
Section: Introductionmentioning
confidence: 98%
“…Some examples are the genes encoding the mitochondrialtargeted porin Mdm10, which is part of the endoplasmic reticulum-mitochondria encounter structure (ERMES) [98], and proteins involved in the calcium signaling machinery (Ca 2+ SM), such as CatSper-like (cation channels of sperm), CaV (membrane voltage-gated Ca 2+ ) and TRP (transient receptor potential) channels [99]. The presence of the ERMES and the Ca 2+ SM in diverse major eukaryotic groups, now including glaucophytes, suggest an ancient origin of these pathways.…”
Section: Phylogenomics Of Cyanophora Paradoxamentioning
confidence: 99%